The impact of the Covid-19 pandemic on teleworking and the logistics of work in Egypt - Mike Leat; Ghada El-Kot (International Business Logistics Journal)
Purpose: The aim of this paper is to investigate the impact of the Covid-19 pandemic on the implementation of teleworking and other flexible work practices, and the logistics of work in Egypt.   Design/Methodology / approach: A review of relevant literature and a survey were conducted. The survey data was collected from a purposive sample of women working in professional and managerial roles in Alexandria and Cairo. The data was collected online between March and May in 2021. The questionnaire was in English. A sample of 1089 employees participated in the study. Data was collected on the perceived impact of the Covid-19 pandemic on employing organizations implementation of teleworking, other flexible work practices and childcare provision.  A range of demographic and employing organization data was collected. Paired comparison and T-test analysis were employed in this study. Findings: The survey results indicated that before Covid-19 implementation of flexible working policies, workplace childcare and childcare allowances was limited. However, Covid-19 is significant in explaining marked increases in the implementation of all the flexible working policies and across all organisational ownership types and size groupings, this is not the case for the policies on childcare where there has been little change to rates of affirmation of implementation. Ownership type and organisational size were also significant in explaining some of the variations in rates of perceived implementation both before and after the pandemic. Research implication/limitation: The study has limitations in terms of the sample being limited to women working in professional and managerial roles in Alexandria and Cairo, the results are therefore not generalisable. Nevertheless, it provides evidence of and confirmed the significant influence of Covid-19 on the incidence of teleworking and other flexible work practices in Egypt. Research is needed to investigate this impact amongst a wider population. Research should also establish employee and employer perceptions of success, satisfaction with the arrangements, the logistics of work in this new environment and plans for the future.     Employers in Egypt had adopted very much the same responses to the pandemic as others in many parts of the world in that Teleworking, WFH and flexitime had all been used to enable continuity of business activity during the pandemic. Greater flexibility in working hours had also been implemented through greater provision of opportunities for reduced hours and part-time working, possibly to cope with reduced levels of activity, as an alternative to laying staff off and as a means of enabling staff to cope with new realities in terms of a blurring of boundaries between work and home life and the demands imposed by children and other family responsibilities.   Practical Implication/limitation: What we have witnessed in Egypt as in many other countries is teleworking, WFH and flexibility as transformation in response to crisis, the test will be to see whether these new modes of working will endure once the pandemic is over and whether the lessons learnt are utilised to inform and cultivate the future of work.  There are some obvious challenges here for the Egyptian business, both in terms of the logistics of ensuring appropriate technical and environmental infrastructure and equipment for employees, but also clearly in transforming management structures, systems, mind-sets and organisational cultures. Originality: There is little evidence of the extent of teleworking and other modes of flexible working and employer childcare provision in Egypt. The survey results reported here constitute important initial findings on the impact of the pandemic on employee perceptions of their employers’ implementation of flexible work and childcare policies, both before and after the Covid-19 pandemic and in organisations varying by ownership and size.